2012
DOI: 10.1371/journal.pone.0030568
|View full text |Cite
|
Sign up to set email alerts
|

Type II NKT Cells Stimulate Diet-Induced Obesity by Mediating Adipose Tissue Inflammation, Steatohepatitis and Insulin Resistance

Abstract: The progression of obesity is accompanied by a chronic inflammatory process that involves both innate and acquired immunity. Natural killer T (NKT) cells recognize lipid antigens and are also distributed in adipose tissue. To examine the involvement of NKT cells in the development of obesity, C57BL/6 mice (wild type; WT), and two NKT-cell-deficient strains, Jα18−/− mice that lack the type I subset and CD1d−/− mice that lack both the type I and II subsets, were fed a high fat diet (HFD). CD1d−/− mice gained the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
93
1
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(103 citation statements)
references
References 45 publications
7
93
1
2
Order By: Relevance
“…As IFN-γ has been associated with insulin resistance in cultured adipocytes (56,57) and in vivo (14,58), these findings suggest that, in contrast to the protective role we observed under LFD conditions, iNKT cells could contribute to the development of insulin resistance under other conditions. Indeed, some recent reports indicate that depletion of iNKT cells can improve insulin sensitivity under HFD conditions (59)(60)(61). The exact role of iNKT cells under HFD conditions is, however, unclear, as other studies, and the present study, failed to detect a prominent effect of iNKT cell depletion on glucose homeostasis (26)(27)(28).…”
Section: Methodscontrasting
confidence: 61%
“…As IFN-γ has been associated with insulin resistance in cultured adipocytes (56,57) and in vivo (14,58), these findings suggest that, in contrast to the protective role we observed under LFD conditions, iNKT cells could contribute to the development of insulin resistance under other conditions. Indeed, some recent reports indicate that depletion of iNKT cells can improve insulin sensitivity under HFD conditions (59)(60)(61). The exact role of iNKT cells under HFD conditions is, however, unclear, as other studies, and the present study, failed to detect a prominent effect of iNKT cell depletion on glucose homeostasis (26)(27)(28).…”
Section: Methodscontrasting
confidence: 61%
“…The roles of iNKT cells and the types of lipid antigens in relation to the time course of obesity have to be elucidated in further study. On the contrary to these two reports, Satoh et al observed that there is no difference in body weight, fat mass, and glucose tolerance between J␣18 KO mice and WT mice after 18 weeks of HFD feeding (32). They compared J␣18 KO mice with commercial B6 mice, rather than littermate control WT mice.…”
Section: Discussionmentioning
confidence: 90%
“…SVCs were incubated with CD16/32 (eBioscience, San Diego, CA), as blocking antibody, for 10 min at 4°C prior to staining with fluorescence-labeled primary antibodies for 30 min at 4°C. Phycoerythrin (PE)-conjugated ␣-GC-loaded CD1d dimer (BD Bioscience, Franklin Lakes, NJ) was prepared as previously described (32). The PE-conjugated immunoglobulin G (IgG) monoclonal antibody (MAb), CD1d dimer, CD3ε MAb, T cell receptor beta (TCR-␤) MAb, and CD4 MAb were purchased from BD Biosciences and CD8 MAb from eBioscience.…”
Section: Methodsmentioning
confidence: 99%
“…Under obese condition, the number of iNKT cells is reduced in AT as well as in peripheral circulation and liver (Lynch et al 2012). However, the exact role of iNKT cells in obesityrelated inflammation and IR is still unclear, as studies on iNKT cell-depleted mice on high-fat diet yielded contradictory results ranging from improvement (Ohmura et al 2010, Satoh et al 2012, Wu et al 2012) to no effect (Kotas et al 2011, Mantell et al 2011 and to worsening (Lynch et al 2012, Schipper et al 2012b of AT inflammation and insulin sensitivity as compared with WT controls. Decreased AT iNKT numbers in obesity might point to a potential role of iNKT cells in the maintenance of antiinflammatory AT profile in lean individuals; nevertheless further research is clearly needed to dissect the significance of iNKT cells in immunometabolic reactions.…”
Section: Nkt Cellsmentioning
confidence: 99%